Acid etching followed by water soaking: a top-down strategy to induce highly reactive substrates for electrocatalysis. Issue 22 (22nd February 2023) - Guo, Yanling; Xue, Min; Pan, Zhongqin; Huo, Xiao-Lei; Bao, Ning; Zhou, Qingwen
Abstract : Taking advantage of the acid etching and water soaking method for in situ synthesis of autologous NiFe LDH, we have developed a top-down strategy for preparing efficient and self-supporting multifunctional electrodes with autologous catalyst–support features. Abstract : A top-down strategy using acid etching followed by water soaking is utilized to in situ synthesize autologous NiFe LDH nanosheets on NiFe foam without other metal ions, oxidizing agents or heating steps. The NiFe foam serves as both the metal source and substrate, and the obtained nanosheets are firmly anchored on the foam. The obtained ultrathin nanosheet arrays could greatly increase the electrocatalytic active sites. This factor together with the synergistic effect between Fe and Ni simultaneously leads to an enhanced catalytic effect for water splitting and urea oxidation. This strategy could be scaled up to pave a viable way for low-cost fabrication of highly efficient electrodes for electrocatalysis.